2022
DOI: 10.1038/s41598-022-17477-5
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the hypothalamo-neurohypophysial system and activation of vasopressin neurones attenuates hyperalgesia in a neuropathic pain model rat

Abstract: Arginine vasopressin (AVP) is a hypothalamic neurosecretory hormone well known as an antidiuretic, and recently reported to be involved in pain modulation. The expression kinetics of AVP and its potential involvement in the descending pain modulation system (DPMS) in neuropathic pain (NP) remains unclear. We investigated AVP expression and its effects on mechanical and thermal nociceptive thresholds using a unilateral spinal nerve ligation (SNL) model. All rats with SNL developed NP. Intensities of enhanced gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…AVP is produced in two distinct populations of neuroendocrine neurons in the PVH of the human hypothalamus: magnocellular AVP neurons and parvocellular corticotropin-releasing factor (CRF)/AVP co-expressing neurons (18). Chronic pain increases AVP secretion in the PVH of rodents, in addition to chronic restraint stress and glucocorticoid deficiency (19,20). Baba et al reported that neuropathic pain increases the mRNA levels of AVP not only in the magnocellular PVH and SON but also in the parvocellular PVH (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AVP is produced in two distinct populations of neuroendocrine neurons in the PVH of the human hypothalamus: magnocellular AVP neurons and parvocellular corticotropin-releasing factor (CRF)/AVP co-expressing neurons (18). Chronic pain increases AVP secretion in the PVH of rodents, in addition to chronic restraint stress and glucocorticoid deficiency (19,20). Baba et al reported that neuropathic pain increases the mRNA levels of AVP not only in the magnocellular PVH and SON but also in the parvocellular PVH (19).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain increases AVP secretion in the PVH of rodents, in addition to chronic restraint stress and glucocorticoid deficiency (19,20). Baba et al reported that neuropathic pain increases the mRNA levels of AVP not only in the magnocellular PVH and SON but also in the parvocellular PVH (19). AVP in the parvocellular PVH is involved in the impairment of water diuresis and hyponatremia via regulation of renal aquaporin-2 protein levels and localization in epithelial cells of the renal collecting ducts in glucocorticoid deficiency (21).…”
Section: Discussionmentioning
confidence: 99%